2019
DOI: 10.1590/2237-6089-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

A critical literature review on emotional intelligence in addiction

Abstract: Introduction Emotional intelligence (EI) has been defined as the ability to perceive, understand, use and manage emotions. Studying EI could potentially be useful in understanding addictive behaviors as well as for designing and planning interventions. Objectives To conduct a critical review on EI impairment in addiction disorders. Methods MEDLINE/PubMed, Google Scholar, Cochrane, LILACS, and SciELO databases were searched. Articles that used the standardized Mayer-Salovey-Caruso Emotional Intelligence Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It has effects on learning, relationships, social, occupational, and psychological well-being and draws its explanatory power from socially challenging opportunity theory (Zeidner et al, 2009). It is associated with aggressive behavior (Qualter et al, 2019), mental illness (e.g., depression, anxiety disorders, bipolar disorder, aggressive behavior; alcohol and substance abuse; Brackett et al, 2011;Hertel et al, 2009;Kaypaklı & Tamam, 2019;Leite et al, 2019;Lizeretti et al, 2012;Mayer et al, 2008;Mikolajczak et al, 2009;Trinidad & Johnson 2002), and academic performance (MacCann et al, 2020). It is based on cognition, in contrast to self-esteem, which is based on affect (Roberts et al, 2001).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…It has effects on learning, relationships, social, occupational, and psychological well-being and draws its explanatory power from socially challenging opportunity theory (Zeidner et al, 2009). It is associated with aggressive behavior (Qualter et al, 2019), mental illness (e.g., depression, anxiety disorders, bipolar disorder, aggressive behavior; alcohol and substance abuse; Brackett et al, 2011;Hertel et al, 2009;Kaypaklı & Tamam, 2019;Leite et al, 2019;Lizeretti et al, 2012;Mayer et al, 2008;Mikolajczak et al, 2009;Trinidad & Johnson 2002), and academic performance (MacCann et al, 2020). It is based on cognition, in contrast to self-esteem, which is based on affect (Roberts et al, 2001).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…It is referring the capacity to recognize feelings of self and others, to motivate ourselves and to manage emotions well in ourselves and our relationships. An extensive review of 7 articles revealed that emotional intelligence was very less in people with drug abuse [4]. Further the motivation of substance abuse patients is also very important to be examined.…”
Section: Emotional Intelligence Motivation and Dysfunctional Attitude...mentioning
confidence: 99%
“…In addition to the association of alexithymia with addictive practices, the literature mentions emotional intelligence (EI) as a dimension that can control or affect addiction [ 29 , 30 ]. EI is defined as the ability to monitor own and others’ feelings and emotions, discriminate between this information, and use it to guide thinking and decisions [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is hypothesized that people with higher EI have better control of their lives and better health outcomes. Moreover, higher EI is associated with better control of impulses and better management of addictions [ 30 ], while lower levels of EI can be associated with higher alcohol use disorder and smoking.…”
Section: Introductionmentioning
confidence: 99%